ROBOTICS MAKING LEARNING EASIER - Maria Tavares Gomes, Cláudia (Revista Gênero e Interdisciplinaridade, 2023)
The present work was developed to explain the current technological transformations in the school environment and how these technologies can collaborate in the interaction of students in learning. It is notorious that human beings live daily with technological changes that affect and modify our study routine, work, coexistence and communication both in the classroom and outside of it. One of these transformations is the growth and expansion of the internet, a technological tool that has drastically changed the way students think and the way they relate to the world, fostering professional, psychological, emotional aspects in the school environment and the consequences that these technological transformations cause. in students’ lives. Educational technology, in addition to inserting a new way of teaching in education, provides experiences on how to work with information technology, the internet and programming within the classroom. Using the LOGO language for this, a program that interacts with school contents, develops students’ intelligence and reasoning, modifies concepts and forms new thoughts through programming, in addition to being an interesting subject, conducive to disseminating new knowledge through interaction of contents. schools and the use of technology.